Potential of Non-Coding RNA as Biomarkers for Progressive Supranuclear Palsy. - Simoes, Fabio A; Joilin, Greig; Peters, Oliver; Schneider, Luisa-Sophie; Priller, Josef; Spruth, Eike Jakob; Vogt, Ina; Kimmich, Okka; Spottke, Annika; Hoffmann, Daniel C; Falkenburger, Björn; Brandt, Moritz; et al. (MDPI AG, 2022)
Objective markers for the neurodegenerative disorder progressive supranuclear palsy (PSP) are needed to provide a timely diagnosis with greater certainty. Non-coding RNA (ncRNA), including microRNA, piwi-interacting RNA, and transfer RNA, are good candidate markers in other neurodegenerative diseases, but have not been investigated in PSP. Therefore, as proof of principle, we sought to identify whether they were dysregulated in matched serum and cerebrospinal fluid (CSF) samples of patients with PSP. Small RNA-seq was undertaken on serum and CSF samples from healthy controls (n = 20) and patients with PSP (n = 31) in two cohorts, with reverse transcription-quantitative PCR (RT-qPCR) to confirm their dysregulation. Using RT-qPCR, we found in serum significant down-regulation in hsa-miR-92a-3p, hsa-miR-626, hsa-piR-31068, and tRNA-ValCAC. In CSF, both hsa-let-7a-5p and hsa-piR-31068 showed significant up-regulation, consistent with their changes observed in the RNA-seq results. Interestingly, we saw no correlation in the expression of hsa-piR-31068 within our matched serum and CSF samples, suggesting there is no common dysregulatory mechanism between the two biofluids. While these changes were in a small cohort of samples, we have provided novel evidence that ncRNA in biofluids could be possible diagnostic biomarkers for PSP and further work will help to expand this potential.
Peer reviewed: True
Funder: My Name’5 Doddie Foundation
Funder: Marion Brownridge
Funder: PSP Association
Keywords: Article; progressive supranuclear palsy; PSP; biomarker; non-coding RNA; RNA-seq